Complete Genome Sequence of Houston Virus, a Newly Discovered Mosquito-Specific Virus Isolated from Culex quinquefasciatus in Mexico - Cigarroa Toledo, Nohemi; Baak Baak, Carlos Marcial; Cetina Trejo, Rosa C.; Córdova Fletes, Carlos; Martinez Nuñez, Mario A.; Talavera Aguilar, Lourdes G.; García Rejón, Julián Everardo; Torres Chable, Oswaldo M.; Suzan, Gerardo; Blitvich, Bradley J.; Machain Williams, Carlos; Stewart, Frank J. (2018)
ABSTRACT We fully sequenced the genome of Houston virus, a recently discovered mosquito-associated virus belonging to the newly established family Mesoniviridae. The isolate was recovered from Culex quinquefasciatus in southern Mexico, which shows that the geographic range of Houston virus is not restricted to the United States in North America.